False Positive 18F-FDG Positron Emission Tomography Findings in Schwannoma—A Caution for Reporting Physicians - Boré, Paul; Descourt, Renaud; Ollivier, Luc; Le Roux, Pierre-Yves; Abgral, Ronan (Frontiers in Medicine, 2018)
Schwannoma is a rare source of false-positive 18-fluorodeoxyglucose (18-FDG) uptake in Positron-emission tomography (PET/CT), inducing potential errors for the staging of several solid cancer, with consequence in patient management. This clinical case reports the situation of a patient undergoing a 18FDG-PET/CT for initial staging of an ovarian adenocarcinoma. We found a high paramediastinal hypermetabolic mass suspicious of remote extension or secondary synchronous primitive tumor. The biopsy finally reveals a histopathology of Schwannoma, allowing the patient to be eligible for a surgical procedure of her ovarian adenocarcinoma by rejecting the hypotheses of malignancy.